The Effect of Parents' Educational Background and School Qualifications on Student Learning Behavior in Indonesia - Fitri April Yanti; Riyanto Riyanto; Didik Suryadi (Yayasan Keluarga Guru Mandiri, 2024)
Students who have good learning behavior will be good learners in the future. It is essential to identify the influence of educational background and parental school qualifications on students' learning behavior, which is part of the child's progress in the future. Thus, the main objective of this study is to explore the influence of educational background and parental school qualifications on students' learning behavior. This study adopted a comparative causal study with a 4 x 3 factorial design and used a purposive sampling method. The sample consisted of 430 students from educational backgrounds whose parents graduated from elementary, junior high, high school, and undergraduate, and from schools with superior, very good, and good qualifications. Exploration of educational background and parental school qualifications was carried out on the learning behavior of low-class students. Data were collected through a three-part questionnaire on parental educational background, students' school qualifications, and a learning behavior assessment scale. The results show that parental background influences students' learning behavior, but school qualifications do not. However, school qualifications can support good learning behavior changes.